LIFE SKILLS EDUCATION IN INCREASING THE INDEPENDENCE OF STUDENTS PURSUING PACKAGE C THROUGH THE SPNF SKB TRENGGALEK - Suwarnoto Suwarnoto; Hikmah Eva Trisnantari; Imam Suwaktus Su’jai (Jurnal Inovasi Penelitian, 2020)
The background of the research in this thesis is based on population data in Trenggalek district, it is found that the population of productive age with low education (not graduating from school) has an unemployment rate that is higher than those who have completed education. The research focuses in this thesis are: (1). How is the personal skills ordering system in increasing the independence of package C students at SPNF SKB Trenggalek (2). How is the social skills booking system in increasing the independence of package C students. (3). What is the system for ordering intellectual skills in increasing the independence of package C students (4). How is the vocational proficiency ordering system in increasing the independence of package C students. The results of the research are (1). The personal skill formation system in increasing the independence of package C students at SPNF SKB Trenggalek is a very important skill, even the first and foremost skill that students must have, where personal skills are behaving in accordance with religious, social, and religious norms. law, have faith in God Almighty, have noble character, are just, honest, commendable, have a work ethic, are responsible and can be trusted. (2).Social skills formation system in increasing the independence of package C students: Social skills for students have characteristics, namely being open, easy to socialize / communicate well with others, superiors, customers / customers and relate to their environment / community the surroundings. (3). The system for building intellectual skills in increasing the independence of package C students: Where this skill implies the ability to analyze simply, think logically, the ability to make decisions, explore good ideas, the ability to dare to try in their field scientifically . (4). Vocational skills formation system in increasing the independence of package C students: Vocational skills (vocational skills), namely the ability to choose jobs, job training, mastering competencies, mastering skills, applying technology, carrying out work processes and producing goods and services that can ultimately improve their standard of living and be able to compete with DU / DI.